(untitled) (Research, Society and Development, 2020)
This article aims to report the experience - under the perspective of interdisciplinarity - of the performance of a dentist of primary health care in a committee to confront COVID-19 in a city in the interior of Bahia. For the development of this study, a descriptive study was carried out, an experience report type that critically presents the actions developed by a dentist of Primary Health Care in a municipality in the interior of Bahia in the planning and actions committee to cope with COVID -19 at the municipal level, from March to August 2020. The study scenario was the municipality of Pedrão, located in the state of Bahia, about 131 km from the capital, Salvador. The performance of the dental professional in the coronavirus coping committee in the municipality brought the creation of documents and protocols as main results, and it was possible to organize the flow of care ensuring equity in care, as well as the protection of patients and professionals, with no To date, no professional in the oral health team has been infected by the new virus. It was evident that facing a pandemic in the context of Primary Health Care, especially in poorer locations, requires interdisciplinary and interprofessional positioning to effectively cope, guaranteeing the safety of the population and also of the professionals directly or indirectly involved in the infection control.